A’uwẽ (Xavante) Hunting Calls: A Vocal Repertoire for Ethnozoological Communication and Coordination in the Brazilian Cerrado - James R. Welch (Ethnobiology Letters, 2020)
Group hunting is a productive subsistence activity for many Indigenous peoples with adequate access to territorial and game resources. A’uwẽ (Xavante) group hunts can involve large numbers of individuals coordinating group hunting efforts over large areas. A’uwẽ group hunting and hunting with fire are sophisticated endeavors requiring years of preparation, ample discussion, and post-hunt analysis. Their hunting calls are stylized expressions following established vocal conventions to communicate complex information over long distances between hunters in order to follow, flush, dispatch, and carry game. This discussion is based on recordings provided by the late A’uwẽ elder and leader Tsidowi Wai'adzatse’ in 2006. He wished that the calls be documented so younger individuals will have means to recall them. I address how Indigenous A’uwẽ hunters in the Brazilian cerrado communicate over long distances with hunting calls that encode rich ethnozoological information. After introducing the topic and context, I begin with a presentation of five ethnozoological calls Tsidowi demonstrated, which he considered the complete repertoire of A’uwẽ hunting calls. Following these short descriptions, I discuss some of the vocal qualities observed in the calls (without conducting a full linguistic analysis), the ethnozoological information they encode, and their prospects for continued use into the future within the context of group hunting with fire.